Economic And Investment Feasibility Comparison Between Electric And Conventional Delivery Vehicles: Case Study Of Pt Pos Indonesia, Karawang Branch - Isnian Adiwijaya; Agus Purnomo; Melia Eka Lestiani (LP2M IAIN Palopo, 2025)
Purpose: This study aims to compare the economic and financial feasibility of electric vehicles (EVs) and conventional vehicles (CVs) in tertiary distribution operations at PT Pos Indonesia, focusing on two operational units: KCU Karawang and KCU Cirebon. Methods: A quantitative comparative approach was applied using Total Cost of Ownership (TCO) and investment appraisal indicators, including Net Present Value (NPV), Internal Rate of Return (IRR), Benefit–Cost Ratio (BCR), and Payback Period (PP). Operational data such as fuel consumption, maintenance, insurance, tax, and depreciation were analyzed under a five-year economic life cycle. Results: The findings show that EVs consistently outperform CVs across all major financial indicators. EVs reduce annual energy costs by up to 80%, significantly lower maintenance and tax expenses, and generate positive NPV values in both locations. IRR for EVs exceeds the 5% discount rate—9.35% in Karawang and 11.2% in Cirebon—while BCR values remain above 1. Payback periods for EVs are 4.4 years in Karawang and 4.3 years in Cirebon. Conversely, CVs show negative NPV, BCR < 1, and no recoverable payback period. Implications: The results highlight the strong financial viability of adopting EVs within Indonesia’s logistics sector, supporting strategic fleet electrification for long-term cost efficiency. The findings also reinforce national sustainability policies promoting low-carbon transportation and provide evidence-based insights for future investment decisions in logistics operations.